On markets and morality: Revisiting Fred Hirsch - Carvalho, Luís Francisco; Rodrigues, João (Review of Social Economy, 2006)
This article argues for the continuing relevance of Fred Hirsch's The Social Limits to Growth (1976), valued as a critical analysis of the consequences of markets on the moral fabric of society. Two concepts that are fundamental to Hirsch—the commercialization bias and the depleting moral legacy—will be scrutinised. We further claim that this book, by emphasizing the tendency to market expansion and the corresponding commodification of increasing spheres of social life, while simultaneously acknowledging its adverse consequences on the motivational appeal of social and moral norms, offers insights that justify revisiting it.
Keywords: HIRSCH, Fred; double movement; markets; morality; neoliberalism; second great transformation; social economy

Karl Polanyi on the Limitations of Formalism in Economics - Stanfield, James Ronald; Carroll, Michael C.; Wrenn, Mary V. (Choice in Economic Contexts, 2006)
This chapter examines Karl Polanyi's critique of formalism in economics and his case for a more institutional economics based upon a reconstitution of the facts of economic life on as wide an historical basis as possible. The argument below reviews Polanyi's argument with regard to the relation between economic anthropology and comparative economics, the contrast between the formalist and substantive approaches to economic analysis, the notion of an economistic fallacy, the most important limitations of the conventional formalist economics approach, and the nature and import of the new departure that Polanyi envisioned. James Ronald Stanfield, Michael C. Carroll, Mary V. Wrenn (2006), Karl Polanyi on the Limitations of Formalism in Economics, in Donald C. Wood (ed.) Choice in Economic Contexts (Research in Economic Anthropology, Volume 25) Emerald Group Publishing Limited, pp.241 - 266
Keywords: economic anthropology; formalism

Is There an Opportunity to Establish the Social-Capitalism in the Post Socialist Transition? - Losonc, Alpar (Panoeconomicus, 2006)
Recently Claus Offe has put the question that concerns the fate of the European model of social capitalism: can the model of social capitalism survive the European integration in the context of certain contemporary tendencies? Offe has presupposed that the mentioned model is challenged by the processes of globalisation and the integration of the post socialist countries into the European Union. The working hypothesis of the article is that there is an opportunity to provide a coherent answer to this question. The article consists of two parts. In the first part the author starts with the Polanyi's socio-economic theory and emphasises the importance of this approach for the analysing of the tendencies of capitalism in Western Europe and in the post socialist countries. The author argues that with the Polanyi's theory we are able to explicate the forms of the embedded liberalism in Western Europe after 1945 and the orientation of non-embedded neo-liberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. Despite the tendencies of the globalisation projected by neo-liberalism, the central element of the social capitalism, namely, the welfare state, remains with the dimensions of the continuity. In the next part the author points out that there is an asymmetrical structure between the Western-Europe and non-Western part of Europe concerning the socialisation of capitalism. The neoliberalisation in accordance with the model of the transfer of ideal-type of capitalism is more strongly implemented in the countries of transition. In addition, the mentioned theoretical approach provides opportunities to explain the failures of implementing of neo-liberalism in the post socialist countries. On the basis of the endorsing of the socio-economic aspects we can address the issue pointed out by Offe.
Keywords: consumer economics; education and training; health; poverty; property rights; provision and effects of welfare programs; social security and public pensions; socialist institutions and their transitions; socialist systems and transitional economies: political economy; welfare, well-being, and poverty: government programs

Commercialisation, inequality and the limits to transition in health care: a Polanyian framework for policy analysis - Mackintosh, Maureen (Journal of International Development, 2006)
The effects of commercialised health care in embedding, exacerbating and legitimating social and economic inequality are at the root of widespread and recurrent resistance to commercialisation in health. In low income developing countries suffering generalised poverty, and notably in Sub-Saharan Africa, liberalisation of largely unregulated clinical provision has created a substantially informalised, fee-for-service primary health sector which is exclusionary, low quality and under stress. This article argues against a policy assumption that health systems constitute a sector that can benefit like other commodities from liberalisation. Health care is better understood as a ‘fictional commodity’ in the Polanyian sense: inappropriate for full commodification, producing intensely perverse effects when provided on competitive markets, and therefore requiring planning and social constraint. If managed effectively, integrated health systems—like redistributive land reform and effective labour protection—can support a broader economic transition that avoids extremes of inequality; conversely if treated simply as a transitional sector, health systems can make exclusion and inequality much worse. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: Africa, Sub-Saharan; economic structure; equality; health care reform; liberalism; medical care; medical policy

An institutionalist perspective on the future of the capitalist world-economy - Özçelik, Emre; Özveren, Eyüp (Journal of Economic Issues, 2006)
The term world-economy in our title must have already given a hint to the careful reader of our purpose in writing this paper: We intend to bridge institutional economics with world-systems analysis in order to enhance the global applicability of the former. World-economy is a term used by Fernand Braudel and Immanuel Wallerstein and means a space defined by the existence of a single division of labor (coexistent with multiple States) whereas world economy would indicate the arithmetic summation of national economies each of which ... In this paper, we elaborate Polanyi's concept of embeddedness so as to construct an institutionalist framework to understand the contemporary world-economy. We contend that embeddedness can be deployed to analyze the so-called "global governance model" (GGM) as the most recent liberal recipe.
Keywords: embeddedness; global governance model; world-economy

The Market, Mind and Rationality. From Vienna to Paris and Back - Rotstein, Abraham (Revue européenne des sciences sociales, 2006)
The mention of the great city of Vienna conjures up the many legacies of music, art and philosophy which it nurtured. But as important as any of these is the more prosaic legacy of the Austrian economists ranging from C. Menger to F. von Hayek. And for some, Vienna may conjure up as well, the debate that K. Polanyi had with these economists in the 1920s. However paradoxical it may seem, it was by virtue of this debate, carried on directly and indirectly over a lifetime, that Polanyi was first and foremost an Austrian, or rather an Austrian «in mirror image ». This was true not only by virtue of the years of his life and his work in Vienna, but more so because he was drawn into and remained a protagonist in the debate around the fundamental issues first raised by the Austrian economists. Menger and his followers E. von Bohm-Bawerk, and L. von Mises had established and diligently pursued much of the agenda of the debate. F. von Hayek was the important representative of this school in recent decades. The particular topic launched by von Mises in 1920 was whether a socialist economy was at all viable without the direction provided by market prices. Regulated or administered prices were bound to lead to economic confusion and the misallocation of resources he maintained.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; MISES, Ludwig von; history of economic thought; regulation; socialist economy